Multi-scale study of the integrated use of the carbohydrate fractions of sugarcane bagasse for ethanol and xylitol production. (January 2021) - Antunes, Felipe A.F.; Thomé, Lucas C.; Santos, Júlio C.; Ingle, Avinash P.; Costa, Cassiano B.; Anjos, Virgilio Dos; Bell, Maria J.V.; Rosa, Carlos A.; Silva, Silvio S.Da
Abstract: A multi-scale study of sugarcane bagasse (SB) pretreatments and integrated developments for use of its carbohydrates portions for ethanol and xylitol production, are presented. In a first approach, after SB acid hydrolysis, hemicellulosic ethanol production was investigated, verifying ethanol yield of 0.31 g/g and volumetric productivity (QP ) of 0.1 g/L.h. Xylitol production was also studied, showing xylitol yield and QP of 0.61 g/g and 0.38 g/L.h, respectively. Thus, remaining cellulignin from acid pretreatment was submitted to alkaline hydrolysis followed by Semi-Simultaneous Saccharification and Co-fermentation in sequential processes to ethanol production, by using mixture of SB hemicellulosic and enzymatic hydrolysate as carbon source, verifying QP of 0.6 g/L.h. Moreover, a biomass multi-scale study was conducted by analysis of MEV, X-Ray, FTIR and Ramman Spectroscopy, verifying clear changes in SB structure along each pretreatment. These novel approaches indicated the potential of these integrated use of SB carbohydrates portion for bioproducts obtaining from SB in sustainable processes. Graphical abstract: Image 1 Highlights: Hemicellulosic and enzymatic sugarcane bagasse hydrolysate:large available source. Multi-scale study of sugarcane bagasse pretreatments: developments for sugars use. Use of acid SB hydrolysate to adjust the enzymatic hydrolysis pH solution. Chemical-enzymatic-fermentation processes conducted in same reactor. Mixture of C5 and C6 hydrolysates as a potential approach for ethanol production.